Suppression of mICAT in Mouse Small Intestinal Myocytes by General Anaesthetic Ketamine and its Recovery by TRPC4 Agonist (-)-englerin A - Mariia I. Melnyk; Mariia I. Melnyk; Mariia I. Melnyk; Dariia O. Dryn; Dariia O. Dryn; Dariia O. Dryn; Lina T. Al Kury; Dmytro O. Dziuba; Alexander V. Zholos (Frontiers Media S.A., 2020)
A better understanding of the negative impact of general anesthetics on gastrointestinal motility requires thorough knowledge of their molecular targets. In this respect the muscarinic cationic current (mICAT carried mainly via TRPC4 channels) that initiates cholinergic excitation-contraction coupling in the gut is of special interest. Here we aimed to characterize the effects of one of the most commonly used "dissociative anesthetics", ketamine, on mICAT. Patch-clamp and tensiometry techniques were used to investigate the mechanisms of the inhibitory effects of ketamine on mICAT in single mouse ileal myocytes, as well as on intestinal motility. Ketamine (100 µM) strongly inhibited both carbachol- and GTPγS-induced mICAT. The inhibition was slow (time constant of about 1 min) and practically irreversible. It was associated with altered voltage dependence and kinetics of mICAT. In functional tests, ketamine suppressed both spontaneous and carbachol-induced contractions of small intestine. Importantly, inhibited by ketamine mICAT could be restored by direct TRPC4 agonist (-)-englerin A. We identified mICAT as a novel target for ketamine. Signal transduction leading to TRPC4 channel opening is disrupted by ketamine mainly downstream of muscarinic receptor activation, but does not involve TRPC4 per se. Direct TRPC4 agonists may be used for the correction of gastrointestinal disorders provoked by general anesthesia.